2000
DOI: 10.1203/00006450-200009000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Diagnosis of Pneumothorax Is Late: Use of Trend Data and Decision Support Might Allow Preclinical Detection

Abstract: Pneumothorax in the newborn has a significant mortality and morbidity. Early diagnosis would be likely to improve the outlook. Forty-two consecutive cases of pneumothorax that developed after admission to a tertiary referral neonatal medical intensive care unit over 4 y from 1993 to 1996 were reviewed. The time of onset of the pneumothorax was determined by retrospective evaluation of the computerized trend of transcutaneous carbon dioxide (tcpCO 2 ) and oxygen tensions. The timing of the occurrence in the not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 16 publications
1
43
0
2
Order By: Relevance
“…Therefore, it is not surprising that we observed significant cerebral damage in both groups of asphyxiated animals. Moreover, pneumothorax is far more frequent in newborns than in any other period of life (23,32,33), and the brain of the newborn piglet is comparable both histologically (34) and electrophysiologically (35) with that of human infants at 36 -38 wk of gestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is not surprising that we observed significant cerebral damage in both groups of asphyxiated animals. Moreover, pneumothorax is far more frequent in newborns than in any other period of life (23,32,33), and the brain of the newborn piglet is comparable both histologically (34) and electrophysiologically (35) with that of human infants at 36 -38 wk of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical status of the animals worsened continuously, and by the end of 1 h after the induction of pneumothorax, gasping, bradyarrhythmia, arterial hypotension, hypoxemia, and severe combined acidosis had developed. The pneumothorax was then relieved, and the response to therapy was controlled by transillumination (Wild M4000 fiberscope, Heerburgg, Switzerland) of the thorax (18,22,23). Asphyxiated animals were randomly divided into two groups.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the early identification of a pneumothorax could be of great importance to optimize management and minimize neurological impairment. 18,22 Limitations There were several limitations in our study. We did not evaluate brain pathology post mortem; therefore the severity of brain injury in these piglets with experimental pneumothorax is unknown.…”
Section: Changes In Carotid Hemodynamics and Oxygen Delivery When Pnementioning
confidence: 93%
“…However detrimental cardiac and/or cerebral effects may precede the clinically significant pneumothorax. Indeed, McIntosh et al 18 reported that the clinical diagnosis of pneumothorax was late, occurring when neonates decompensated. Therefore, we designed this study to explore the temporal changes in hemodynamics and oxygenation, including surrogates of cerebral measurements (carotid arterial flow and oxygen delivery) during a progressive pneumothorax in neonatal piglets.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2a shows the pattern of cold stress 2 , seen within days of instituting our trend monitoring system. More difficult, but fairly consistent, has been the picture of the occurrence of a pneumothorax where the transcutaneous carbon dioxide level sharply increases usually at the same time as a sharp decrease in the transcutaneous oxygen 3 (Fig 2b). We believed that our system helped in management but wish to see whether there was any difference in outcome.…”
Section: Trend Patterns In Physiological Datamentioning
confidence: 74%